Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1039/b309961j
|View full text |Cite
|
Sign up to set email alerts
|

The role of coordination chemistry in the development of target-specific radiopharmaceuticals

Abstract: There is a great current interest in developing target-specific radiopharmaceuticals for early detection of diseases and radiotherapy of cancers. This critical review will focus on the role of coordination chemistry in the development of target-specific radiopharmaceuticals. It will also discuss the recent development in technetium, copper, gallium, indium, yttrium and lanthanide chemistry, as well as analytical tools for quality control and characterization of radiolabeled small biomolecules (159 references).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
260
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(271 citation statements)
references
References 133 publications
2
260
0
6
Order By: Relevance
“…Such a strategy is commonly reported as bifunctional chelate (BFC) approach. 20 Hence, starting from the already known potent and selective TSPO ligand CB86 (Chart 1), 15 we designed a new namely,[2][3][4][5][6][7][8] 1), where, the di(2-picolyl)amine moiety could be used for the synthesis of coordination complexes containing a metallo drug to be used in diagnosis and therapy.Preliminarily, we performed in vitro studies on the newly synthesized TSPO-selective BFC ligand CB256 in order to assess its affinity toward TSPO. In addition, since it is wellknown that TSPO ligands are able to induce apoptosis, we also investigated the cytotoxic activity and the ability to cause morphological changes of the mitochondrion and of the nucleus, the collapse of the mitochondrial membrane potential (ΔΨ m ), and alterations of the cell cycle progression in C6…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a strategy is commonly reported as bifunctional chelate (BFC) approach. 20 Hence, starting from the already known potent and selective TSPO ligand CB86 (Chart 1), 15 we designed a new namely,[2][3][4][5][6][7][8] 1), where, the di(2-picolyl)amine moiety could be used for the synthesis of coordination complexes containing a metallo drug to be used in diagnosis and therapy.Preliminarily, we performed in vitro studies on the newly synthesized TSPO-selective BFC ligand CB256 in order to assess its affinity toward TSPO. In addition, since it is wellknown that TSPO ligands are able to induce apoptosis, we also investigated the cytotoxic activity and the ability to cause morphological changes of the mitochondrion and of the nucleus, the collapse of the mitochondrial membrane potential (ΔΨ m ), and alterations of the cell cycle progression in C6…”
mentioning
confidence: 99%
“…Such a strategy is commonly reported as bifunctional chelate (BFC) approach. 20 Hence, starting from the already known potent and selective TSPO ligand CB86 (Chart 1), 15 we designed a new namely,[2][3][4][5][6][7][8] 1), where, the di(2-picolyl)amine moiety could be used for the synthesis of coordination complexes containing a metallo drug to be used in diagnosis and therapy.…”
mentioning
confidence: 99%
“…It was reported that introduction of the polyethylene glycol (PEG) linker can improve not only tumor uptake but also excretion kinetics of 125 I-and 18 F-labeled c(RGDyK) and 64 Cu-labeled E[c(RGDyK)] 2 (25)(26)(27)(28). PKM linkers and their applications to improve the excretion kinetics of radiolabeled small biomolecules have been reviewed recently (13,24,(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…The RGD peptide serves as "vehicles" to carry radionuclide ( 99m Tc, 18 F and 64 Cu) to the integrin α v β 3 overexpressed on tumor cells and activated endothelial cells of the tumor neovasculature. 99m Tc is the choice of radionuclide for single photon computed tomography (SPECT) and planar imaging due to its optimal nuclear properties (half-life, abundance and energy of gamma photons) and easy availability at low cost (12)(13)(14). For the 99m Tc-labeling, 6-hydrazinonicotinic acid (HYNIC) has been used as a bifunctional coupling agent while tricine and a water-soluble phosphine or pyridine analog are used as coligands to prepare ternary ligand 99m Tc complexes [ 99m Tc(HYNIC-SU016)(tricine) (L)] (L = ISONIC (isonicotinic acid), TPPTS (trisodium triphenylphosphine-3,3′,3″-trisulfonate, and PDA (2,5-pyridinedicarboxylic acid)) (1-3).…”
Section: Introductionmentioning
confidence: 99%
“…A number of biomolecules, such as monoclonal antibodies and peptides, have been exploited as carriers for radionuclides; some have been granted approval by the Food and Drug Administration. [45] Of all the vitamins investigated as carriers for target delivery, vitamin B 12 is probably the least studied. Earlier works with 57 Co-labeled cobalamins aimed to elucidate the accumulation of vitamin B 12 in transplanted tumors.…”
Section: Diagnostic Vitamin B 12 -Metal Conjugatesmentioning
confidence: 99%